Demeter - Abu Lebdeh, Raghad; Qasrawi, Nura (My University, 2020)
Agriculture is an import aspect of life, farmers all over the world have trouble providing the best care for their plants and crops. So our idea came from this point of view which is to make farmers’ life easier and at the same time provide the best care for plants. The most important parts of this project is to come up with a smart plant which can move from the shade towards the sunlight when it needs to. In addition, while keeping a track of the humidity levels in soil using sensors so when those levels reach below a certain threshold, the system will be notified to provide water. The plant while be placed on cart that moves according to the sunlight direction which will be detected using LDR Leds and other components; a humidity sensor will also be used in the soil and this will be connected to irrigation system which will open and closes according to the sensor. The idea of this project has been done before but separately, as the two talked about features were done individually, each in different projects. In our project, we are combining the two features in one system which will provide a full plant caring system.